Web App– and Text Message–Based Patient Education in Mohs Micrographic Surgery—A Randomized Controlled Trial. Issue 7 (July 2018) - Hawkins, Spencer D.; Koch, Sarah B.; Williford, Phillip M.; Feldman, Steven R.; Pearce, Daniel J.
Abstract : BACKGROUND: Consent and wound care (WC) videos are used for education in Mohs micrographic surgery (MMS). Postoperative text messaging is poorly studied. OBJECTIVE: Develop and evaluate perioperative resources for MMS patients—video modules (DermPatientEd.com ) and postoperative text messaging (DermTexts.com ). MATERIALS AND METHODS: A study was conducted on 90 MMS patients. Patients were randomized 1:1:1:1 to videos with text messages, videos-only, text messages-only, or control. Primary outcomes included preoperative anxiety and knowledge of MMS and postoperative care. The secondary outcome included helpfulness/preference of interventions. RESULTS: Patients experienced a 19% reduction in anxiety as measured by a visual analog scale after the MMS video ( p = .00062). There was no difference in knowledge after the WC video ( p = .21498). Patients were more likely to report the WC video "very helpful" when compared with the pamphlet in understanding postoperative WC ( p = .0016). Patients in text messaging groups were not more likely to report the service as "very helpful" when compared with the pamphlet ( p = .3566), but preferred to receive WC instructions by text message for future visits ( p = .0001). CONCLUSION: These resources proved helpful and effective in reducing preoperative anxiety. Patients prefer text message–based WC instructions over pamphlets after experiencing the service, but do not find them more helpful. Abstract : Supplemental Digital Content is Available in the Text.